Effect of Xylanase Supplementation and Particle-Size on Performance of Guinea Fowl Broilers Fed Wheat-Based Diets - Tufarelli, V.; Dario, M.; Laudadio, V. (International Journal of Poultry Science, 2007)
The effect of xylanase enzyme supplementation and particle-size in wheat (Triticum durum)-based diets was studied in guinea broilers from 29 to 91 days of age. Weekly body weight, gain, feed consumption and Feed Conversion Ratio (FCR) were determined. Was formed 4 groups, each fed: diet A (ground wheat with enzyme); diet B (ground wheat without enzyme); diet C (ground wheat passed through 3 mm sieve, pelleted and after crumbled with enzyme): diet D (crumbled wheat without enzyme). The highest body weights values were recorded by guinea fowls fed diet C. Birds fed diet B have shown low mean values of body weight. Subjects fed diet C were obtained values of mean body weight different (p